Predation of livestock by puma (Puma concolor) and culpeo fox (Lycalopex culpaeus): numeric and economic perspectives - Gallardo, Giovana; Pacheco, Luis F.; Rios, Rodrigo S.; Jiménez, Jaime E. (THERYA, 2020)
Predation on livestock by wild carnivores represent large economic losses worldwide. Livestock predation by puma (Puma concolor) and culpeo fox (Lycalopex culpaeus) represents not only a problem for the Sajama National Park (SNP) management in Bolivian highlands, but also for the conservation efforts of these predators. At SNP we quantified: 1) The frequency of attacks by puma and culpeo fox on domestic livestock. 2) The effect of socio-ecological variables on the predation of livestock by these predators. 3) Estimated the losses of livestock due to other causes and compared these with the losses resulting from predation. We expected that the probability of a carnivore attack on a ranch would increase with higher livestock densities, lower abundance of wild prey, good habitat characteristics for carnivores, and low rates of husbandry and would decrease in smaller ranches and/or in areas near human settlements. We monitored predation and other causes of livestock mortality in 33 ranches for one year and estimated biomass of livestock and wild prey and monetary losses. Predators killed 183 livestock (2.3 ± 0.9 % of the animals/ranch) equivalent to 4,215 USD and averaging 21.8 ± 19.6 % of a family’s annual income. Another 354 domestic animals died of causes unrelated to predation (201 adults and 153 yearlings), averaging 4.3 ± 4.5 % of livestock holdings per ranch. The probability of puma attacks increased with ranch size, livestock biomass and distance to the nearest town but decreased with husbandry during the dry season, while their frequency increased with ranch area. The probability of fox attacks decreased with Bofedal area, livestock biomass and better husbandry during the dry season, whereas their frequency increased when wildlife biomass decreased. Although the losses due to predation were low, the impact on the herders’ economy was important. Stock mortality resulting from malnutrition, diseases, and accidents was twice as high as through predation. To reduce losses due to livestock predation and diseases, we advocate managing livestock by reducing group numbers, providing better veterinary assistance, increasing surveillance of herds during grazing events –especially during the rainy season– and through an adequate management of young animals in corrals.